Review of Disruptive Technologies in 3D Bioprinting - Joshua G. Hunsberger; Pearly Pandya; Molly K. Mulligan; Davide Marotta; Lorenzo Moroni; Maxim Shusteff; Grace Brogan; Mathew Brovold; James Yoo; Jacob Koffler; Isac Lazarovits; Salil Desai; et al. (Current Stem Cell Reports, 2025)
Purpose of Review The purpose of this review is to share insights from recognized experts in 3D biopriniting on the recent advances in these technologies discussed during a recent workshop held in conjunction with the 2024 ISS National Laboratory Research and Development Conference (ISSRDC). We seek to answer how microgravity can be used as a disruptor to make further advances not possible through conventional means. Recent Findings This review will cover current efforts underway to use microgravity for 3D bioprinting. For instance multi-levitation biofabrication technology funded under the EU PULSE project is currently being used to create cardiovascular 3D in vitro models to better mimic cardiac and vascular physiology compared to organoids. These types of models could be expanded to other organ systems and disease models to use the environment of microgravity to unlock new signaling pathways to cure disease. Summary The major takeaway from this review is that microgravity will unlock new opportunities for 3D bioprinting that were simply not possible using conventional means. We provide forward looking answers to what microgravity will inspire from advanced biomaterials to new disease models to even creating a knowledge hub for 3D bioprinting to launch new platforms at record speeds.